Mueller-Weiss syndrome, An unexpected cause of mid foot pain in adolescents - Dana Alomran; Karim Gaber; Waleed Kishta (Journal of Orthopaedic Reports, 2024)
Case: This is a case report of a 16-year-old male patient with chronic midfoot pain and rigid pes planus. The main differential diagnosis included tarsal coalition, accessory navicular and residual Kohler's disease, but imaging modalities confirmed Mueller-Weiss syndrome, a rare condition of spontaneous osteonecrosis of the navicular bone typically found in adults. To the best of our knowledge, this is the first reported case of Mueller-Weiss syndrome in a patient younger than 18 years old. Surgical intervention was carried out for the case and complete resolution of symptoms was achieved in the first 3 months. Conclusion: This case report underscores the importance of appropriate imaging modalities and individualized treatment plans for each patient with midfoot pain, particularly in younger populations with rigid pes planus. It also highlights the need for increased awareness of rare conditions such as Mueller-Weiss syndrome in the differential diagnosis of midfoot pain in adolescents.